Keberlangsungan UMKM Di Pekanbaru Dalam Aspek Numerikal - Nur Fitriana; Dimas Darma Putra; Nesya Audi M (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Micro, Small and Medium Enterprises (MSMEs) are the only center of the people's economy in Indonesia, and Pekanbaru is the only province with a strong MSME business environment. Low performance and productivity are two problems that are often raised in MSMEs, but one phenomenon that often arises in this problem is the ability of MSME business actors to maintain their business, as well as develop and grow to be successful. This is caused by a lack of knowledge regarding mental accounting and calculation skills. The aim of this research is to see and find out how influential mental accounting and numeracy skills are on the sustainability of MSMEs in Pekanbaru City. This research is quantitative research which includes a large amount of primary data, namely data collected by this researcher using validity, reliability and hypothesis tests. Data from the analysis results show that mental accounting and numeracy skills have a significant effect on the resilience of MSMEs in Pekanbaru City.